1996
DOI: 10.1021/jf9506702
|View full text |Cite
|
Sign up to set email alerts
|

Formation of 3-Hydroxy-4,5-dimethyl-2(5H)-furanone (Sotolone) from 4-Hydroxy-l-isoleucine and 3-Amino-4,5-dimethyl-3,4-dihydro-2(5H)-furanone

Abstract: The proposed formation of 3-hydroxy-4,5-dimethyl-2(5H)-furanone (sotolone) from 4-hydroxy-l-isoleucine (1) and the corresponding lactone 3-amino-4,5-dimethyl-3,4-dihydro-2(5H)-furanone (2) by thermally induced oxidative deamination was corroborated. The formation of sotolone was studied in model systems by reacting 1 or 2 with different carbonyl compounds in a phosphate buffer at pH 5 at 100 °C for 1 h. The amount of sotolone was quantified by stable isotope dilution assays using 13C2-labeled sotolone as inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 14 publications
0
50
1
Order By: Relevance
“…On the other hand, Blank et al (27) found that sotolone was generated in model systems by thermally induced oxidative deamination of HIL through 3-amino-4,5-dimethyl-3,4-dihydro-2(5H)-furanone, using different carbonyl compounds as carbonyl reactant. In the present work we were unable to find the HIL oxidative deamination product (10). However, the compound 3-amino-4,5-dimethyl-2(5)-furanone, previously found in L. helvus (29), with a molecular weight and mass spectrum close to those of sotolone, was clearly present in the hairy root cultures ( Figure 5; Table 2).…”
Section: Time Course Of Growth Of Hairy Roots In Conical Flaskscontrasting
confidence: 58%
See 2 more Smart Citations
“…On the other hand, Blank et al (27) found that sotolone was generated in model systems by thermally induced oxidative deamination of HIL through 3-amino-4,5-dimethyl-3,4-dihydro-2(5H)-furanone, using different carbonyl compounds as carbonyl reactant. In the present work we were unable to find the HIL oxidative deamination product (10). However, the compound 3-amino-4,5-dimethyl-2(5)-furanone, previously found in L. helvus (29), with a molecular weight and mass spectrum close to those of sotolone, was clearly present in the hairy root cultures ( Figure 5; Table 2).…”
Section: Time Course Of Growth Of Hairy Roots In Conical Flaskscontrasting
confidence: 58%
“…From the synthetic pathways postulated for sotolone formation (12,26,(56)(57)(58), it has been suggested that this compound might originate from HIL. This hydroxylated amino acid is usually present in T. foenumgraecum (59,60) and L. helvus (29), a mushroom from Europe.…”
Section: Time Course Of Growth Of Hairy Roots In Conical Flasksmentioning
confidence: 99%
See 1 more Smart Citation
“…This molecule has great flavouring potential, with an estimated threshold value of 0.02 ng L À1 in air and of 0.3 lg kg À1 in water, which are quite low (Blank & Schieberle, 1993;Blank et al, 1997). Its precursors in the seeds are suspected to be 4-hydroxyisoleucine, which is the major amino acid present and whose content decreases during germination, and its lactone [3-amino-4,5-dimethyl-3,4-dihydro-2(5H)-furanone] (Blank, Lin, Fumeaux, Welti, & Fay, 1996;Blank et al, 1997;Girardon et al, 1986). However, other molecules are also involved in the strong odour characteristic of fenugreek, as other potent aroma compounds have been reported in fenugreek using different modes of 0308-8146/$ -see front matter Ó 2009 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…L-Isoleucine, found in micromolar concentration (189 μM; Table 1) in the culture liquid, is an obvious precursor of L-hydroxyisoleucine, which was identified in the culture medium (Figure 2). This compound may, in turn, have served as a precursor of the corresponding oxoacid, which would then cyclize to sotolon (9) and the related furanone (10) (Figures 1, 3c). [15] The same oxoacid could explain the presence of 4,5-dimethyl-dihydrofuran-2-one (4).…”
Section: Resultsmentioning
confidence: 99%